Redox and Coordination Behavior of the Hexaphosphabenzene Ligand in [(Cp*Mo)2(μ, η6:η6‐P6)] Towards the "Naked" Cations Cu+, Ag+, and Tl+. Issue 44 (4th September 2015) - Fleischmann, Martin; Dielmann, Fabian; Gregoriades, Laurence J.; Peresypkina, Eugenia V.; Virovets, Alexander V.; Huber, Sebastian; Timoshkin, Alexey Y.; Balázs, Gábor; Scheer, Manfred
Abstract Although the cyclo‐P6 complex [(Cp*Mo)2(μ, η6:η6‐P6)] (1) was reported 30 years ago, little is known about its chemistry. Herein, we report a high‐yielding synthesis of 1, the complex 2, which contains an unprecedented cyclo‐P10 ligand, and the reactivity of 1 towards the "naked" cations Cu+, Ag+, and Tl+. Besides the formation of the single oxidation products 3 a, b which have a bisallylic distorted cyclo‐P6 middle deck, the [M(1)2]+ complexes are described which show distorted square‐planar (M=Cu(4 a), Ag(4 b)) or distorted tetrahedral coordinated (M=Cu(5)) M+ cations. The choice of solvent enabled control over the reaction outcome for Cu+, as proved by powder XRD and supported by DFT calculations. The reaction with Tl+ affords a layered two‐dimensional coordination network in the solid state.